Field transplantation of the bivalve Scrobicularia plana along a mercury gradient in Ria de Aveiro (Portugal): uptake and depuration kinetics - Cardoso, P. G.
The bioaccumulation and depuration capabilities ofmercury by the edible bivalve Scrobicularia plana was studied in a coastal lagoon (Ria de Aveiro, Portugal) through a transplantation experiment. Little information on this topic is available in the literature, especially concerning different tissues' responses to contaminant exposure, but the present study is one of the fewworks that can surpass this knowledge gap. Organisms froma reference areawere transplanted to two different contaminated areas in the Ria de Aveiro. In both areas, the bivalves (i.e., entire organism, digestive gland and the rest of the organism) presented a similar saturation model of mercury accumulation, the digestive gland being the tissue that reached the highest concentrations after 25 days of exposure to the contaminant. During this short uptake period, the transplanted organisms reached 20–30% of the concentrations observed in resident contaminated organisms. After the exposure period, the organisms were transplanted to a clean area for more than 25 days of depuration. At the end of the transplantation period, organisms lost approximately 50% of theirmercury body burden (60%: the entire organismand digestive gland; 35%: gills and 40%: the rest of the organism) and the ones from the least contaminated site almost reached the concentrations recorded in the reference area. So, the results suggest that S. plana is a promising biomonitoring species, since it accumulates the contaminant in a considerable extent quite rapidly and at the same time it has a low metal retention capacity (low biological half-life) when exposed to clean sediments.